HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT KEMANDIRIAN LANSIA DALAM PEMENUHAN AKTIVITAS SEHARI-HARI - Kosasih, Ikhwan; Khasanah, Imroâatul (Akademi Keperawatan Pamenang, 2013)
In the age of modernization the relationship between young people with parents (elderly) are increasingly tenuous, so they have little time to think about the elderly. The objective of the research was to know the relation of social support for families with elderly grade independent in the fulfillment of daily activities at Sub-village of kudu, village of Jantok district of Purwoasri Kediri regency in 2011.The research design used analytic with approach of cross sectional. The population was the entire family that had the elderly in the sub village of kudu, village of Jantok district of Purwoasri Kediri regency, amount to 65 respondents. Sample amount to 56 respondents who fulfilled the criteria for inclusion and exclusion. Intake of sample used simple random sampling. The research instrument used a questionnaire, and then analyzed by using Spearmans correlationBased on the research results, most families provide social support to the elderly amount to 30 respondents (53.6%) and has a degree of independence of elderly with a total amount to 32 respondents (57.1%). From the results of Spearmans correlation test found significant value 0.000 <0.05, which means Ho was rejected. This means that there was relation of social support for families with elderly grade independent in the fulfillment of daily activitiesKnowledge was one of the factors that affect social support and social support was one of factor that affects the independence of the elderly. The existence of a good knowledge about the importance of social support to the elderly will be able to improve the provision of social support of elderly families, and good social support can increase the independence of elderly Keyword : Social support of family, elderly independence